Kajian Aspek Reproduksi Ikan Famili Cichlidae di Danau Batur, Bali - Sukmayanti, Ni Ayu Ajeng Meirina; Pertami, Nyoman Dati; Ulinuha, Devi (Current Trends in Aquatic Science, 2024)
Studies on the reproductive aspects of fish of the Cichlidae family in Lake Batur have never been carried out. This study aims to determine the reproductive aspects of fish of the Cichlidae family in Lake Batur. Sampling was carried out from November to December 2021. Laboratory analysis was carried out from October to December 2022. This research used descriptive and quantitative methods. Sampling using purposive sampling method at three points. The fishing gear used is gill nets with a size of 0.5; 1.0; 1.5; 2.0; 2.5; and 3.0 cm and bubu. The gill nets and traps were installed in the afternoon (16.00 WITA) and removed the next day (07.00) WITA. Samples found during data collection consisted of 222 individuals including four species, namely: midas cichlid ( Amphilophus citrinellus ), three spot cichlid ( Amphilophus sp.), mozambique tilapia ( Oreochromis niloticus ), and nile tilapia ( Oreochromis mossambicus ). The level of gonadal maturity (TKG) of the four species is varied (I-V) each month, with the average gonadal maturity index (IKG) for female Cichlidae family fish being higher than males and the peak spawning time occurring in November and December (rainy season). The sex ratio of fish in the Cichlidae family of the four species was only midas cichlid ( Amphilophus citrinellus ) found in an unbalanced condition and nile tilapia ( Oreochromis niloticus ) in a balanced condition. As for the species of three spot cichlid ( Amphilophus sp.) and mozambique tilapia (Oreochromis mossambicus) in December and November were not analyzed because the female sex was not found.